Cambridge leaner's dictionary network CD- ROM (Cambridge University Press, 2004)
A new edition of the acclaimed Cambridge Learner's Dictionary, fully updated to include new words. New mini-panels show words that go together (collocations). The CD-ROM has a new, easier-to-use interface, exercises related to Cambridge exam levels, and includes QUICKfind and SUPERwrite (interactive reading and writing tools) as well as the unique SMART thesaurus which turns the dictionary into a thesaurus at the click of a button.